Act Versus Impact: Conservatives and Liberals Exhibit Different Structural Emphases in Moral Judgment. - Hannikainen, Ivar R.; Miller, Ryan M.; Cushman, Fiery A. (Ratio, 2017)
Conservatives and liberals disagree sharply on matters of morality and public policy. We propose a novel account of the psychological basis of these differences. Specifically, we find that conservatives tend to emphasize the intrinsic value of actions during moral judgment, in part by mentally simulating themselves performing those actions, while liberals instead emphasize the value of the expected outcomes of the action. We then demonstrate that a structural emphasis on actions is linked to the condemnation of victimless crimes, a distinctive feature of conservative morality. Next, we find that the conservative and liberal structural approaches to moral judgment are associated with their corresponding patterns of reliance on distinct moral foundations. In addition, the structural approach uniquely predicts that conservatives will be more opposed to harm in circumstances like the well-known trolley problem, a result which we replicate. Finally, we show that the structural approaches of conservatives and liberals are partly linked to underlying cognitive styles (intuitive versus deliberative). Collectively, these findings forge a link between two important yet previously independent lines of research in political psychology: cognitive style and moral foundations theory.